Solution of a two-dimensional parabolic model problem in a degenerate angular domain - Ramazanov, M.I.; Gulmanov, N.K.; Kopbalina, S.S. (Bulletin of the Karaganda University. Mathematics Series, 2023)
In this paper, the boundary value problem of heat conduction in a domain was considered, boundary of which changes with time, as well as there is no the problem solution domain at the initial time, that is, it degenerates into a point. To solve the problem, the method of heat potentials was used, which makes it possible to reduce it to a singular Volterra type integral equations of the second kind. The peculiarity of the obtained integral equation is that it fundamentally differs from the classical Volterra integral equations, since the Picard method is not applicable to it and the corresponding homogeneous integral equation has a nonzero solution.